The Role of Green innovation in Competitive Advantage Mediated by Innovation Performance in MSMEs in Sumenep Regency - Wibisono, Aryo; Ghufrony, Ahmad; Alfiah, Nur Inna; Gienardy, Melda (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
Main Objective The purpose of this study is to see the impact between green innovation and innovation performance variables on competitive advantage directly and the indirect influence between green innovation on competitive advantage through innovation performance.  Method This study uses a quantitative model and uses Part Least Square analysis with a sample of 100 MSME respondents. Main Findings from the research results, it was found that there is a direct influence between green innovation and innovation performance variables on competitive advantage and there is an indirect influence between green innovation on competitive advantage through innovation performance.  Theory and Practical Implications The results of the study can provide research development from green innovation, and provide an overview of the factors that have an impact on competitive advantage. Novelty The novelty of this research shows the influence between green innovation on innovation performance that no one has previously researched, as well as the use of research models to examine MSMEs.